An effective method of bulk materials moisture measurement using capacitive sensors. (December 2020) - Zabolotnyi, Oleksandr; Koshevoi, Mikola
Abstract: When we speak about capacitance moisture meters for bulk materials we have to face with different values of dielectric permittivity for different bulk materials in dehydrated state, what causes a method error that can be named 'type uncertainty'. Besides, different varieties of the same material have different values of dielectric permittivity, which depend from geographical origin, processing conditions etc. It can be hardly predicted automatically and type uncertainty can be compensated only in separate situations with the help of preliminary calibration. Main tasks of the research are to develop new comparison principle of moisture measurement with better accuracy due to effective compensation of physical, chemical and granulometric composition influence on the result of moisture measurement, develop new primary and secondary instrument transducers. Moisture sensor consists of four measuring capacitors. Two of them should be filled with a sample, which moisture content should be determined, and other pair of measuring capacitors should be filled with a same substance, but previously dehydrated. Mathematical models, developed to take into account granulometric composition of a bulk material were used to carry out a comparison analysis for three types of instrument measuring transducers. Obtained results proved that suggested principle of moisture measurement provides effective compensation of granulometric composition influence. Developed measuring principle had been experimentally tested what helped to confirm that it provides two times better compensation of different physical and chemical composition for different materials in comparison with the direct comparison method. Highlights: Moisture measurement of bulk materials is a task of current importance for agriculture. Moisture meter's calibration is a problem because reference moist substances are usually absent. Suggested method of moisture measurement provides effective "type uncertainty" compensation. Suggested method provides effective compensation of granulometric composition influence. Experimental researches confirmed that suggested moisture measurement method is effective.